Mechanism of Strategic Decision Making in Emergency Situations of Terrorist Attacks in Indonesia - Nurhidayat; Adrianus Meiliala; Anggi Aulina Harahap (Technium Social Sciences Journal, 2024)
Terrorism is a global phenomenon experienced by all countries including Indonesia, manifested in terrorist attacks that involve violence as a main element with the motivation to achieve political, ideological, and certain belief goals. The threat of potential massive terrorist attacks continues to evolve to this day. Each era shows a tendency in terms of ideology and also types of terrorist attacks. In different times, it is not impossible to have the potential for attacks in different forms. Terrorist attacks that occur in a country can pose a threat to the stability of all aspects of life, thus requiring competent handling by looking at how the mechanism of strategic decision making in Indonesia faces emergency situations of terrorist attacks. Reflecting on the experience of handling the Bali Bombing I, this research was conducted with a qualitative approach based on literature studies and interviews with sources consisting of academics, practitioners, and strategic observers in the issue of terrorism using rational choice theory and criminal policy as the basis for writing. Through the study conducted, the authors found that although Indonesia has experience in handling terrorist actions, the readiness from the capacity aspect needs to be matured, especially in dealing with terrorist attacks. Therefore, a strategic and uncomplicated decision-making mechanism needs to be formulated immediately through a clear command flow or delegation of authority that applies when emergency conditions of terrorist attacks occur.